Combined Task and Physical Demands Analyses towards a Comprehensive Human Work Model. (September 2014) - Farrell, Philip S. E.; Tack, David W.; Nakaza, Edward T.; Bray-Miners, Jordan; Farrell, Cristopher M.
Task analyses and physical demands analyses are combined to identify common and extreme postures and postural sequences, durations, frequency, and forces for Griffon Helicopter aircrew tasks, mission phases, and whole missions. The result is a comprehensive model of tasks and associated physical demands from which one can estimate the accumulative neck loads and moments caused by Night Vision Googles usage. Combining task and physical demands analyses yields a methodology for building a model of human work where information processing and physical demands are equally important for finding effective solutions to work issues.